2015
DOI: 10.5301/tj.5000396
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT to Predict Optimal Primary Cytoreductive Surgery in Patients with Advanced Ovarian Cancer: Preliminary Results

Abstract: Fluorodeoxyglucose-PET/CT shows high sensitivity but suboptimal specificity in the characterization of ovarian masses. However, PET/CT may play a role in noninvasively selecting patients with EOC who can benefit from primary CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…76% (n ¼ 19) of these lesions were mucinous tumours and this was not surprising as our results found PET scans to be less useful in mucinous tumours (p ¼ .009) probably due to the large amounts of non-viable mucin which would not be metabolically active. This result was similar to previous studies by De Vos et al and Whiteford et al who reported lower sensitivity of FDG-PET in mucinous cancers as compared with non-mucinous cancers (58-60% versus 92-96%) [23,24,28]. In the remaining two patients, both conventional imaging and PET scans did not definitively pick up peritoneal disease but they were found to have peritoneal lesions at laparotomy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…76% (n ¼ 19) of these lesions were mucinous tumours and this was not surprising as our results found PET scans to be less useful in mucinous tumours (p ¼ .009) probably due to the large amounts of non-viable mucin which would not be metabolically active. This result was similar to previous studies by De Vos et al and Whiteford et al who reported lower sensitivity of FDG-PET in mucinous cancers as compared with non-mucinous cancers (58-60% versus 92-96%) [23,24,28]. In the remaining two patients, both conventional imaging and PET scans did not definitively pick up peritoneal disease but they were found to have peritoneal lesions at laparotomy.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the degree of FDG-avidity can be helpful in differentiating malignant from benign tumours in cases of CT or MRI-indeterminate lesions. To our knowledge, there have only been a few studies evaluating the usefulness of PET-CT in patients undergoing CRS and HIPEC and none in the Asian context [9,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible to determine whether a patient can be optimally debulked until the cytoreduction procedure is underway, thus limiting the value of laparoscopic features as a preoperative predictor for suboptimal cytoreduction 16 . We also did not include specific findings of radiologic studies, including CT scan 9 , 17 , 18 and PET/CT 19 - 21 , as predictors for cytoreductive outcomes. The reason is that use of specific imaging results before surgical resection is difficult in clinical application, and they have not been validated in large prospective randomized trials 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous studies have revealed that preoperative cancer antigen 125 (CA125) level is associated with the results of cytoreductive surgery 9 , 12 - 15 . Specific laparoscopic 16 , computed tomography (CT) 9 , 17 , 18 , and positron emission tomography/computed tomography (PET/CT) findings 19 - 21 have been suggested as means by which the prediction of cytoreductive surgery outcomes can be improved. Although several studies have suggested potential tools for predicting outcomes of cytoreductive surgery, controversial results have also been reported, and thus their use as valuable predictors in the clinic is limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, the range of specificity of ld PET/CT was reported to be 67.0%–94.6% based on Alessi et al . [19] and Tanizaki et al .,[17] respectively.…”
Section: Evidence Synthesismentioning
confidence: 99%